Is Intracytoplasmic Sperm Injection Success Affected by the Testicullar Histopathology in Nonobstructive Azoospermic Patients? - Sokmensuer, Lale Karakoc; Kose, Mesut; Demir, Ahmet; Bozdag, Gurkan; Gokoz, Ozay; Gunalp, Serdar (Sci Printers & Publ Inc, 2015)
OBJECTIVE: To investigate whether the histological changes observed in testicular tissue might be correlated with pregnancy outcome in intracytoplasmic sperm injection testicular sperm. extraction (TESE) cycles in nonobstructive azoospermic patients. Embryo quality was also tested in various types of histology. STUDY DESIGN: We retrospectively analyzed the pathology results of 209 testicular biopsies from nonobstructive azoospermic patients in our assisted reproductive technologies clinic. According to the final pathology reports, the study group was divided into the following categories: Group A (Sertoli-cell-only), Group B (maturation arrest), Group C (hypospermatogenesis), Group D (normal spermatogenesis), and Group E (mixed pattern). RESULTS: Spermatozoa were identified in 114 of 209 cases (54.5%). Sperm retrieval and presence of motile spermatozoa after TESE was highest in normal spermatogenesis and lowest in Sertoli-cell-only groups. Fertilization rate was highest in the normal spermatogenesis and hypospermatogenesis groups. Embryo grades on day 3 were comparable between groups. Clinical pregnancy per embryo transfer was also similar. Both fertilization and clinical pregnancy rates were statistically higher in favor of motile spermatozoa group. CONCLUSION: Testicular histopathology not only gives information regarding the probability of retrieving sperm at TESE, but also is a good predictor of fertilization. Once a motile spermatozoon is identified, the chance of clinical pregnancy might improve probably due to relatively good optimal microenvironment within the testis.
Keywords: assisted reproductive techniques; histopathology; intracytoplasmic sperm injections; reproductive technology; assisted; testicular histopathology; testicular sperm extraction